Roaming freely throughout the Universe Nicolas Baudin's voyage to Australia and the pursuit of science - Fornasiero, Jean; West-Sooby, John (Wakefield Press, 2021)
The Age of Exploration not only paved the way for European conquest and trade, it also widened the horizons of science. By the second half of the eighteenth century, the link between travel and science was so widely acknowledged that it had become routine practice to include naturalists in all major voyages of exploration. The need to study natural phenomena in situ might seem self-evident. Some, however, considered that the main purpose of fieldwork was to collect specimens for the dispassionate examination of specialists back home. Truly meaningful study, they argued, required the kinds of resources that were not available to those in the field. As the renowned French naturalist Georges Cuvier put it, 'it is only in one's study that one can roam freely throughout the universe'. In the context of this debate, Nicolas Baudin's voyage of discovery to Australia (1800-1804), which included both specialist field collectors and aspiring young savants, proved pivotal. Drawing on a range of archival sources, the essays presented here offer fresh perspectives on Baudin's scientific voyagers, their work and its legacy. What emerges is a deeper appreciation of the Baudin expedition's contribution to the pursuit of science, and of those who pursued it
Keywords: Baudin, Nicolas -- 1754-1803; Geschichte 1800-1804; Wissenschaftlicher Fortschritt; Naturwissenschaften; Expedition; Australien; Baudin, Nicolas / 1754-1803 / Travel; Scientific expeditions / Australia; Australia / Discovery and exploration / French; Expéditions scientifiques / Australie; Baudin, Nicolas / 1754-1803; Discoveries in geography / French; Scientific expeditions; Travel; Australia; Aufsatzsammlung